Generative AI and its Transformative Value for Digital Platforms - Wessel, Michael; Adam, Martin; Benlian, Alexander; Majchrzak, Ann; Thies, Ferdinand (Journal of Management Information Systems, 2025)
The emergence of generative artificial intelligence (GenAI) represents a watershed moment in the evolution of digital platforms. The capabilities of this AI technology go beyond traditional AI systems, enabling the autonomous generation of novel outcomes with significant implications for platform value creation, architecture, governance, and stakeholder interactions. We develop an integrative conceptual framework that identifies four key mechanisms through which GenAI transforms digital platforms: intelligent automation, democratization, hyper-personalization, and collaborative innovation. Through intelligent automation, GenAI transforms boundary resources from passive interfaces into active, intelligent mediators of value creation. Democratization systematically lowers barriers to platform participation. Hyper-personalization enables dynamic, individual-level adaptation of platform content. Collaborative innovation transforms platform innovation by making GenAI an active participant in human-AI value co-creation. We use this framework to situate the papers in the special issue and develop a research agenda that explores the transformative impact of GenAI on platform stakeholder relationships.